Analysis Location Quotient of Tourism Supply Using Geoda Approach in Indonesia - Ayu Esteka Sari; Deky Hamdani (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted to identify economic sectors that are the basis of economic competitiveness in the tourism supply sector, in provinces in Indonesia. Descriptive quantitative analysis through secondary data sources derived from the publication of data from the Central Statistics Agency of the Province and National Statistical Agency was carried out using the Location Quotient and Geoda Analysis methods. The results of the study show that in three sectors that are economic benchmarks in tourism offerings based on the Location Quotient method and Geoda analysis. In Accommodation, Food and Beverage sector Bali province is the province with the largest Location Quotient. In the transportation sector, West Sumetara province is the province with the largest Location Quotient. In the communication sector, East Java province is the province with the largest Location Quotient. The results of the research can be used as input for policy makers to formulate economic development strategies, especially in the tourism sector to improve the regional economy.